2022
DOI: 10.38212/2224-6614.3416
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain activates the AMP-activated protein kinase-autophagy pathway to alleviate hepatic lipid accumulation

Abstract: Bromelain, a cysteine protease found in pineapple, is known to exert protective effects against non-alcoholic fatty liver disease (NAFLD); however, the underlying mechanism is unclear. In this study, we aimed to investigate the molecular mechanisms underlying the beneficial effects of bromelain using in vivo and in vitro models. C57BL/6 mice were fed a high-fat diet (HFD) with or without bromelain (20 mg/kg/day) for 12 weeks. We found that treatment with bromelain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A study aiming to investigate the effects of bromelain on glucose uptake in muscle cells in vitro found that bromelain increased the glucose uptake in muscle cells by activating the protein kinase, AMPK. 99 This study further suggested that bromelain might have remarkable potential for the treatment for diabetes by improving the glucose metabolism in muscle cells. 102 Another similar study investigated the effects of bromelain on blood glucose levels in rats with diabetes, and it was found that the daily administration of bromelain for 21 days resulted in a significant reduction in blood glucose levels compared with the control group.…”
Section: Diabetesmentioning
confidence: 68%
See 1 more Smart Citation
“…A study aiming to investigate the effects of bromelain on glucose uptake in muscle cells in vitro found that bromelain increased the glucose uptake in muscle cells by activating the protein kinase, AMPK. 99 This study further suggested that bromelain might have remarkable potential for the treatment for diabetes by improving the glucose metabolism in muscle cells. 102 Another similar study investigated the effects of bromelain on blood glucose levels in rats with diabetes, and it was found that the daily administration of bromelain for 21 days resulted in a significant reduction in blood glucose levels compared with the control group.…”
Section: Diabetesmentioning
confidence: 68%
“…Research has shown that bromelain can activate AMPK in muscle cells, which in turn increases glucose uptake and its utilization by the cells. 99 This might lead to improved glucose metabolism and lower blood glucose levels, which is beneficial for individuals with diabetes. Another mechanism by which bromelain might show anti-diabetic activity is by reducing inflammation and oxidative stress.…”
Section: Diabetesmentioning
confidence: 99%
“…Auriculasin [25] Colon Ca ↓ pAIFM1 [25] Bromelain [60] Colon Ca ↑ ATG5, ATG7 [61], ACSL4 [60] Curcumin [62] Colon Ca ↑ ATF3 [63], ACSL4 [64], IREB2 [63], HMOX1 [65] ↓ SLC7A11, GPX4 [62,64], HIF1A [66], NEDD4 [67,68] Dihydroartemisinin [69] Glioma ↑ ATF4 [70,71], NCOA4 [72], HMOX1 [69] ↓ GPX4, SLC7A11, SLC3A2 [70], FTH1 [73] Dihydroisotanshinone I [74] Glioma ↑ ACSL4 [74] ↓ GPX4 [74] Diplacone [75] Lung Ca DMOCPTL [76] Breast Ca ↓ GPX4 [76] Epigallocatechin gallate [77] Pancreatic Ca ↑ ATF4 [78], ATG5, ATG7 [79], YAP1 [80] ↓ SP1, TP53 [81] Epunctanone [82] Leukemia…”
Section: Ferroptosis Inducersmentioning
confidence: 99%
“…Auriculasin, a Flemingia philippinensis -derived flavonoid, triggers the ferroptosis and apoptosis of colon cancer cells by downregulating the ferroptosis-inhibiting protein, such as phosphorylated AIFM1 [ 25 ]. For bromelain, it suppresses hepatic lipid accumulation by upregulating ferroptosis-inducing proteins, such as phosphorylated ATG5 and ATG7, in the liver of high-fat-diet-fed mice [ 61 ]. In comparison, bromelain inhibits proliferation and induces the ferroptosis of colon cancer cells by upregulating the ferroptosis-inducing ACSL4 gene [ 60 ].…”
Section: Ferroptosis-modulating Natural Productsmentioning
confidence: 99%